Yathrib Jewsâ Language(s): A Study Based on Authentic á¸¤adiá¹¯s - Sbaihat, Ahlam; Albanna, Nama (Al-Jamiah Research Centre, 2017)
A controversial topic of research was the language of the Jews of Yathrib, this research tries to shed light on the controversial issue. Muslim and non-muslim scholars give different explanations. However, none of these theories could determine whether this language is spoken or written. Hadiths of Prophet Muá¸¥ammad indicate three languages; Hebrew, Aramaic and Syriac. For the purpose of this study, the researchers have gathered a repertoire of the authentic hadiths of the prophet related to the topic, accredited and then analyzed them. The results indicate that the Prophet asked Zayd, his translator, to learn Hebrew, which is the language of correspondence and worship of the Jews of Yathrib. Furthermore, the study shows that the language of everyday communication of the Jews of Yathrib was Arabic, which borrowed some worship-related Hebrew terms.[Topik riset ini mencoba mengangkat beberapa isu kontroversi yang terkait dengan bahasa orang Yahudi di Yathrib (Medinah). Berbagai teori dan penjelasan dari akademisi muslim atau Orientalis masih memperdebatkan apakah bahasa tersebut merupakan bahasa lisan atau tulis. Secara eksplisit dalam hadis Nabi terindikasi adanya tiga bahasa yaitu: Ibrani, Aramaik dan Syria. Dalam tulisan ini, peneliti akan mengumpulkan, akreditasi dan analisis hadits Nabi yang autentik terkait dengan topik ini. Kesimpulannya menunjukkan bahwa Nabi memerintahkan Zayd, penerjemahnya, untuk belajar bahasa Ibrani yang mana merupakan bahasa surat â menyurat dan ritual orang Yahudi di Medinah. Oleh karena itu, tulisan ini menunjukkan bahwa bahasa komunikasi sehari-hari orang Yahudi di Medinah adalah bahasa Arab yang diantaranya meminjam beberapa istilah dalam bahasa Ibrani.]Â Â